Youth Economic Empowerment Strategy Based on the Utilization of the YouTube Platform in YouTuber Tapen Bondowoso Village - Fawaid, Yazidul; Ulfah, Mariyah; Masruroh, Nikmatul (LP2M INSURI Ponorogo, 2024)
Tapen Bondowoso village in Bondowoso Regency has undergone digital transformation, evolving into a YouTuber Village driven by the creative endeavors of its youth. This qualitative phenomenological research investigates the use of the YouTube platform in the village, outlines the youth economic empowerment strategy through content creation, and assesses the economic status of youth pre, and post-empowerment. Utilizing snowball techniques, the researchers identified young YouTubers as informants and employed interviews, observations, and documentation. Findings reveal active community participation in YouTube content creation, motivated by economic and environmental factors. The empowerment strategy encompasses enablement, strengthening, protection, support, and maintenance. Post-empowerment, there is a significant positive impact on the economic conditions of youth, evident in improved income and heightened fulfillment of needs. This research highlights the transformative role of YouTube-based empowerment for both individual youths and the broader Tapen village community.